2017
DOI: 10.1167/iovs.16-20618
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Comparison of GWAS, Transcriptome, and Proteomics Studies Highlights Similarities in the Biological Basis of Animal and Human Myopia

Abstract: These findings suggest that genetic and environmental factors control ocular growth via similar biological pathways across species, and support the continued use of animal models for investigating the biological mechanisms underlying human myopia development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 69 publications
4
29
0
Order By: Relevance
“…The TGF-β superfamily of ligands includes BMPs, growth and differentiation factors, anti-müllerian hormone, activin, nodal, and the TGF-β proteins [25]. Signaling begins with the binding of a TGF-β superfamily ligand to a TGF-β type II receptor [26]. The type II receptor is a serine/threonine receptor kinase, which catalyzes the phosphorylation of the type I receptor [25].…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β superfamily of ligands includes BMPs, growth and differentiation factors, anti-müllerian hormone, activin, nodal, and the TGF-β proteins [25]. Signaling begins with the binding of a TGF-β superfamily ligand to a TGF-β type II receptor [26]. The type II receptor is a serine/threonine receptor kinase, which catalyzes the phosphorylation of the type I receptor [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these studies suggested that similar biological processes underlie refractive development in animal models and humans [63].…”
Section: One Of the Leading Causes Of Vision Loss In Several Parts Ofmentioning
confidence: 91%
“…A lot of research has been undertaken to investigate the gene expression patterns that occur during the development of myopia, and a full examination of the genes involved in myopia development is beyond the scope of this review. Analysis has shown that the candidate genes involved in human myopia development display significant overlap with the candidate genes identified in experimental animal models of myopia, indicating these models remain suitable for studying human myopia development (131). It is clear that a large number of genes are upregulated or downregulated during development of or recovery from myopia, some of them in a bidirectional manner.…”
Section: Candidate Genesmentioning
confidence: 99%